Upper respiratory tract infection among the workers of brick kilns of Bhaktapur district. - Kila, Samita (2011)
SUMMARY: Brick kilns are the major contributor to increase air pollution. The CO2, CO, SO2, NO2, TSP, PM in the polluted air highly affects the health of the people who are exposed to it. It mainly leads to respiratory disorders. Most of the brick kilns in the Kathmandu valley are left unmanaged with residential area around it. This causes respiratory disorders among the workers and the local people around the brick kilns. Workers are highly exposed to dust and fumes produced from brick kilns they are more vulnerable to respiratory tract infection. So this study principle objective was to study the prevalence and symptoms related to upper respiratory tract infection among the workers of brick kilns of Bhaktapur district. And along with this study also aimed to assess the period of exposure, health related behaviors including the practice of using PPE and knowledge on PPE among the brick kiln workers. This study was cross-sectional descriptive. There are 64 registered brick kilns in the Bhakapur district in different V.D.Cs, so three V.D.Cs were selected purposively where higher number of brick kilns are located. And brick kilns from the respective V.D.Cs are selected by simple random sampling method. Purposive sampling method was used to collect data from the respondents. The primary data was collected by interview and observation using structured and semi- structured questionnaire and observation checklist. More than half of the respondents accounting for 59 percent have upper respiratory disorder. The highest prevalence was found to be 96 percent for regular cough, 94 percent for sore throat followed by 66 percent for difficulty in breathing, 25.4 percent for running nose, 15.3 percent for body ache, 10.2 percent for chest pain, 5.1 percent for fever and 3.4 percent for headache. Only 32 percent have knowledge on different preventive measures of upper respiratory tract infection. Whereas 11 percent of workers were found to be using PPE for covering nose and mouth. Smoking and alcohol drinking was found to be habitual among 43 percent and 33 percent of the brick kilns workers respectively. Among the 5 brick kilns under the study 4 brick kilns have no provision of safe drinking water. All the brick kilns were found to be using 70 percent of coal, 24 percent of sawdust and remaining 6 percent of wood for brick firing.